THE CORRELATION BETWEEN MOTIVATION BEHAVIOUR AND SPEAKING ABILITY - Diki Maulana; Widya Sri Wahyuni; Detya Siregar (IKIP Siliwangi, 2018)
This researchis aboutthe correlation between motivation behaviour and spekaing abilityat English Students Association. Hence, this research is aimed to find out whether or not there is a significant correlation between motivation behaviour and speaking ability at English Students Association. This research used correlation research design and qualitative research. The instrument is motivation test using questionnaire and speaking test by story telling. The population of this research is English Students Association of IKIP Siliwangi and the sample is 30 students. The data o this research is analysed using pearson product moment correlation coefficient. The degree of correlation between two variables was low with a correlation coefficient of 0.045. the result showed that there was a weak correlation between motivation behaviour and speaking ability at English Students Association.